2015
DOI: 10.1097/opx.0000000000000514
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance of Three Silicone Hydrogel Daily Disposable Lenses

Abstract: Each of the three SiHy DDCLs performed well. Noninvasive tear breakup time was longest and wettability was greater with DT1. C1D had the most conjunctival staining conjunctival indentation. There was no difference between asymptomatic and symptomatic wearers with regard to ocular response and contact lens-related parameters. These results suggest that SiHy DDCLs may be an excellent contact lens modality for the symptomatic patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 44 publications
4
23
0
Order By: Relevance
“…Some authors reported an increase in bulbar redness after 8 h of wear with somofilcon A and narafilcon A material [26]. Other studies showed no changes in redness.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some authors reported an increase in bulbar redness after 8 h of wear with somofilcon A and narafilcon A material [26]. Other studies showed no changes in redness.…”
Section: Discussionmentioning
confidence: 98%
“…[25] Wolffsohn et al showed that tear break-up time over the daily contact lens surface differed between lens types and may have a role in protecting the ocular surface [21]. Several authors did not observe any changes over time in contact lens wearers [21,26,27] using silicone hydrogel daily contact lenses at 8, 12, and 16 h of wear on one day. The findings of this study are in agreement with those found in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…Significant efforts have been made to minimize the impact of SiH materials on the tear film by making the surfaces more wettable; to date, these include surface treatments, internal and external wetting agents, water gradient surfaces and the incorporation of hydrophilic monomers [128]. As a result, the on-eye wettability of SiH materials has been shown to be very similar to that typically observed with hydrogel materials [128,[131][132][133][134].…”
Section: Materials and Surface Properties Of Silicone Hydrogel Contactmentioning
confidence: 99%
“…Three SiH DD contact lenses (delefilcon A, narafilcon A and somofilcon A) were compared in a short-term randomized, cross-over study in both symptomatic and asymptomatic contact lens wearers [133]. All three lens types performed well with respect to surface deposits, wettability, pre-lens noninvasive tear breakup time, lens movement, and centration.…”
Section: Meeting Patient Needs With Contemporary Contact Lens Materiamentioning
confidence: 99%
“…These developments include the invention of silicone hydrogel contact lenses . Silicone hydrogel materials have grown to dominate the contact lens market and have become widely used in the USA and Europe …”
mentioning
confidence: 99%